Human Scalp Electroencephalography Reveals that Repetition Suppression Varies with Expectation - Summerfield, Christopher; Wyart, Valentin; Mareike Johnen, Vanessa; de Gardelle, Vincent (Frontiers in Human Neuroscience, 2011)
Repetitions of a sensory event elicit lower levels of brain activity than its initial presentation (‘repetition suppression’). According to one view, repetition suppression depends on the biophysics of neuronal discharge, and is thus an automatic consequence of stimulus processing (‘fatigue’ model). Another account suggests that repetition suppression depends on the statistical structure of the environment, and occurs when repeated stimuli are less surprising than novel stimuli (‘surprise reduction’ model). In support of the latter view, functional magnetic resonance imaging studies have shown that repetition suppression is modulated by the local probability of repetition. However, single-cell recordings from macaque inferotemporal area (IT) have failed to replicate this finding. Here, we recorded scalp electroencephalography from human participants viewing pairs of faces that repeated (face1-face1) or alternated (face1-face2), in contexts in which repetitions were expected or unexpected. As previously described, event-related potentials in the range of 100-400 ms recorded at posterior electrode sites and at the vertex differed between repetitions and alternations. Critically, at central electrodes, we observed that the difference between repeated and alternating stimuli was attenuated when repetitions were unexpected, as predicted by the surprise reduction model. These findings demonstrate that the modulation of repetitions suppression by repetition probability is observable using direct neural recording methods in human participants, and that it occurs relatively late (>300 ms) post-stimulus. Finally, we found that theta-band (4-8 Hz) spectral power over central electrodes varied with the three-way interaction between of repetition, expectation, and the rate of change of the environment, consistent with recent reports that frontal theta may be a hallmark of learning processes originating in the anterior cingulate and medial prefrontal cortex.